Sealing composite with defective margins, good care or over treatment? results of a 10-year clinical trial - Fernández, Eduardo; Martin, Javier; Vildósola, Patricio; Estay, Juan; Oliveira Júnior, Osmir Batista de [UNESP]; Gordan, Valeria V.; Mjor, Iva A.; Gonzalez, Jeannette; Loguercio, Alessandro D; Moncada, Gustavo (Operative Dentistry, 2014)
Purpose: The objective of this study was to clinically evaluate sealed composite restorations after 10 years and compare their behavior with respect to controls. Methods and Materials: The cohort consisted of 20 patients aged 18 to 80 years with 80 composite restorations. All participants in the sealing and no-treatment groups presented with clinical features for the marginal adaptation that deviated from the ideal and were rated Bravo (United States Public Health Service criteria). Composites with Alfa values for the marginal adaptation were used as the positive control. Results: The marginal adaptation behavior was similar between the sealing and control (+) groups, with a high frequency of Bravo values in the 10th year (80% and 51%, respectively). Most of the no-treatment (-) group maintained the Bravo values (91%) for 10 years, although some restorations (9%) progressed to Charlie values. The anatomy parameter differed significantly between the first and 10th years, with deterioration in all three groups (p,0.05). The secondary caries parameter had a similar behavior in the three groups (p.0.05). Conclusions: Sealing the margins of the composite resin restorations had no significant effect compared with the control groups, under the conditions of this study. Sealing the restorations substantially improved the marginal staining and marginal adaptation parameters, although by the tenth year they were similar to the group without intervention.
Keywords: Composite resin; Marginal Sealing; Clinical trial